Choquet boundary for some subspaces of continuous functions: Dedicated to Professor Heiner Gonska on the occasion of his 70th anniversary. - HODIȘ, Laura; MĂDUȚA, Alexandra (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
We investigate the Choquet boundary for subspaces of parabolic functions and for linearly separating subspaces of continuous functions. The relation of the Choquet boundary with the set of peak points is also investigated. Mathematics Subject Classification (2010): 46A55.